Interlocking joint resistance in rc wall panel using crushed concrete waste aggregate in bending / Nor Shuhadah Sabri - Sabri, Nor Shuhadah (Faculty of Civil Engineering, 2013)
The precast wall panel are used widely for high rise- construction because of the ease and speed of assembly and it has high quality. Connections form the most important part of precast concrete construction Research and developments have been conducted by many researchers, engineers and manufacturers to find the range of solutions, theoretical concepts and design equations for various types of connection. Over 70 million tonnes of natural waste produced from construction industry each year. Crushed Concrete Waste Aggregate (CCwA) is a one product from construction waste and this can make many advantages to construction industries and also global. Two (2) set interlocking stocky wall panels with male and female connection were prepared with the dimensions of 75 mm x 900 mm x 500 mm by using CCwA. The results showed that the differences between interlocking Stocky wall panel (iSWP) of vertical displacement were 82.12% and the lateral displacement between the samples was 92.06% for T1 and 95.67% for T2. The crack pattern of both samples was in shear crack.